PERBANDINGAN DESAIN PENGUJIAN KONSTITUSIONAL PADA MAHKAMAH KONSTITUSI FEDERAL JERMAN DAN INDONESIA - Lailam, Tanto (Universitas Brawijaya, 2023)
This research is based on the weaknesses of constitutional review design in Indonesian and how the best design in Germany. This normative legal research is analysed using legislation and comparative approaches. The results showed that the German and the Indonesian Constitutional Courts had the same design and practice of constitutional review. The German Constitutional Court has complete authority, namely the abstract judicial review, concrete judicial review, and constitutional complaints. While the Indonesian Constitutional Court is only given the abstract judicial review and does not have a concrete judicial review and constitutional complaint authority, in practice, some applications are characterized by both. The design of abstract judicial review between the German and Indonesian Constitutional Courts has the same object of disputes but differences in the party applying. The object of the dispute on the concrete judicial review at the German Constitutional Court is the implementation of laws relating to court cases. The objects of petitions for constitutional complaints are judicial decisions, laws, and others.